2008
DOI: 10.5380/rsa.v9i1.10142
|View full text |Cite
|
Sign up to set email alerts
|

Germinação De Sementes De Pessegueiro-Bravo Sob Diferentes Condições De Luz E Substrato

Abstract: RESUMOO objetivo deste trabalho foi avaliar a influência da luz e de substratos na condução de testes de germinação de Prunus sellowii Koehne. Os testes foram realizados no Laboratório de Sementes Florestais da Universidade Federal do Paraná e constou de dois experimentos: o primeiro envolveu quatro condições de luz (branca, vermelha, vermelha-extrema e ausência de luz) e o segundo, quatro substratos (areia, vermiculita, ágar e rolo de papel toalha). Foram avaliados o índice de velocidade (IVG) e a porcentagem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…When seeds were stratified without the endocarp, most of the cultivars presented 100% germination, except the cultivars Flordaguard, Tsukuba 2 and 3, which presented 93% germination (Table 2). Rodrigues et al (2008) evaluating the germination of seeds of Prunus sellowii Koehne, emphasized that the germination tests should be carried out without the endocarp, aiming to eliminate the physical dormancy caused by the endocarp, which can significantly limit germination potential. In our study, this can be demonstrated by comparing the results of percentage germination and GSI in experiment 1 (Table 1) and experiment 2 (Table 2).…”
Section: Germination Potential Of Seeds Without Endocarpsmentioning
confidence: 99%
“…When seeds were stratified without the endocarp, most of the cultivars presented 100% germination, except the cultivars Flordaguard, Tsukuba 2 and 3, which presented 93% germination (Table 2). Rodrigues et al (2008) evaluating the germination of seeds of Prunus sellowii Koehne, emphasized that the germination tests should be carried out without the endocarp, aiming to eliminate the physical dormancy caused by the endocarp, which can significantly limit germination potential. In our study, this can be demonstrated by comparing the results of percentage germination and GSI in experiment 1 (Table 1) and experiment 2 (Table 2).…”
Section: Germination Potential Of Seeds Without Endocarpsmentioning
confidence: 99%
“…e Vochysia tucanorum Mart. (SILVA et al, 2000;BARBOSA et al, 1999), enquadrando-se na recomendação para a maioria das espécies florestais tropicais, para as quais a temperatura constante de 25 °C encontra-se na faixa ótima para germinação (RODRIGUES et al, 2008).…”
Section: Resultsunclassified